Different mechanisms are involved in oxidative DNA damage and genotoxicity induction by ZnO and TiO2 nanoparticles in human colon carcinoma cells. Issue 7 (October 2015) - Zijno, Andrea; De Angelis, Isabella; De Berardis, Barbara; Andreoli, Cristina; Russo, Maria Teresa; Pietraforte, Donatella; Scorza, Giuseppe; Degan, Paolo; Ponti, Jessica; Rossi, Francois; Barone, Flavia
Highlights We compared ZnO and TiO2 nanoparticle genotoxic potential in relation to oxidative stress. Multiple endpoints for genotoxic detection were analyzed on Caco-2 cells. Both nanoparticles were able to induce ROS and 8-oxodG. Oxidative DNA damage was efficiently repaired only after treatment with TiO2 nanoparticles. Only ZnO nanoparticles induced micronuclei.